HUBUNGAN TINGKAT PENGETAHUAN IBU YANG MEMILIKI BAYI USIA 0-6 BULAN TERHADAP PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS DATUK BANDAR KOTA TANJUNGBALAI TAHUN 2019 - ERLINA ESTHER ROTUA SIRINGORINGO (JURNAL ILMIAH MAKSITEK, 2020)
Exclusive feeding is very important for infants aged 0-6 months because all nutrient content is in breast milk which is very useful. Lack of knowledge of mothers causes in the end mothers provide formula milk that is harmful to the health of babies. Low maternal education level, limited knowledge insight and hereditary tradition are some factors that support the occurrence of the assumption that breast milk alone is not enough as a baby food. As a result, mothers provide various forms of fluid as breast milk substitutes before their babies reach the age of 4 months. The design of research is a correlation of research that is correlated to know the knowledge level relationship of mothers who have an infant aged 0-6 months against the benefit of exclusive BREAST feeding in the Puskesmas Year 2019. That respondents who had good knowledge of 21 people (70%) and provide exclusive breast milk. While having enough knowledge 9 people (16.7%) and 2 people (16.7) provide exclusive ASI and 7 persons (23.4%) Give no exclusive ASI. In this study using the Chi Square test is a hypothesis test on the comparison between the observation frequency the results of the study showed that the relationship of mothers with infants 0-6 months is associated with exclusive BREAST-feeding. In connection with this research is advised to health personnel to provide regular counseling to mothers with infants on the benefits of exclusive breast milk.